Building musical culture in nineteenth-century Amsterdam. The Concertgebouw - Cressman, Darryl (Amsterdam University Press, 2016)
When people attend classical music concerts today, they sit and listen in silence, offering no audible reactions to what they're hearing. We think of that as normal-but, as Darryl Cressman shows in this book, it's the product of a long history of interrelationships between music, social norms, and technology. Using the example of Amsterdam's Concertgebouw in the nineteenth century, Cressman shows how its design was in part intended to help discipline and educate concert audiences to listen attentively - and analysis of its creation and use offers rich insights into sound studies, media history, science and technology studies, classical music, and much more.